The Multiple Roles of Women In Improving The Family Economy in Kradenan Hall - Nisa’, Khoirun; Sudrajat, Arief (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The advancement of technology and the advent of digitalization have changed perspectives. Previously, women were labeled as solely responsible for the family's needs at home. However, now both men and women have equal roles in earning a living. Women's dual roles have emerged as a smart strategy for improving family financial well-being. Furthermore, they are a way to realize family dreams that would otherwise be impossible if they relied solely on men or husbands. Increasing needs and uncontrolled prices have pushed a number of women in Kradenan Hamlet into jobs outside the home as housewives. This study employed a qualitative method with a phenomenological approach to gain detailed insight into the experiences of the research subjects. Data were collected through in-depth interviews, observation, and documentation of women who perform dual roles in Kradenan Hamlet. This study utilized data analysis by Miles and Huberman, including data reduction, data presentation, and conclusion drawing. The results of this study examine the various meanings they share in strengthening the family economy, using Alfred Schutz's theory.